When clouds raise an eyebrow – the case for a new supplementary cloud feature 'Supercilium'. (8th November 2022) - Graham, Edward; Pretor‐Pinney, Gavin
Abstract : In 2017, the World Meteorological Organization accepted 12 revisions to the International Cloud Atlas, including the introduction of a new supplementary cloud feature, asperitas . Here, we present compelling photographic evidence gathered over recent years, which argues the case for an additional new cloud feature, ' supercilium ', to be also considered for inclusion in the Atlas, which at present lacks a precise category or description of these clouds. ' Supercilium ' are short‐lived cloud features, which appear in turbulent airflow over, and to the immediate lee of, steep mountain peaks during periods of strong mountain summit level winds.